Influence of scrotal bipartition on spermatogenesis yield and sertoli cell efficiency in sheep - Rodrigues,Ramon T.G.A. (2016)
Abstract With the objective to assess the effect of scrotal bipartition on spermatogenesis in sheep, the testes were used from 12 crossbred rams of sheep farms in the municipality of Patos, Paraíba, Brazil, distributed into two groups: GI with six rams with scrotal bipartition, and GII with six rams without scrotal bipartition. The testicular biometry was measured and the testes were collected, fixed in Bouin and fragments were processed to obtain histological slides. The spermatogenesis yield and the Sertoli cell efficiency was estimated by counting the cells of the spermatogenetic line at stage one of the seminiferous epithelium cycle and the Sertoli cells. The results were submitted to analysis of variance with the ASSISTAT v.7.6 program and the mean values were compared by the Student-Newman-Keuls test (SNK) at 5% significance. The testicular biometric parameters did not show statistical difference (p>0.05) between the groups. The meiotic, spermatogenetic and Sertoli cell efficiency were higher in bipartitioned rams (p<0.05), while the mitotic yield did not differ (p>0.05) between GI and GII. The results indicated that there is superiority in the spermatogenetic parameters of bi-partitioned rams, suggesting that these sheep present, as reported in goats, indication of better reproductive indices.